The Impact of Venture Capital and Private Equity Investments on Innovation in Chosen States in Central-Eastern Europe - Banaś, Grzegorz; Bill, Rafał (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The article looks at the level of innovation as measured by the Global Innovation Index and the level of investment through venture capital (VC) and private equity (PE) in Poland, Romania, Bulgaria, Hungary and Czech Republic. To measure the performance of innovation, data was taken from Global Innovation Index reports published by INSEAD; VC and PE were estimated using the accounts of European Private Equity and Venture Capital Association. The research verifies the argument that PE and VC investments have an impact on state innovation if the level of those investments is above the average of other contributors. We tested the correlation for the years 2009-2011, which are considered the peak of the economic crisis.